'If This Was a Normal Situation': Challenges and Potentials for Deliberative Democratic Peacebuilding in Kosovo's Emerging Governance Networks. (21st February 2017) - Delaney, Aogán; Van Der Haar, Gemma; Van Tatenhove, Jan
Summary: The link between public administration and conflict resolution is traditionally understood through the 'democratic peace' thesis, which holds that war is less likely in democracies than in non‐democracies. Limited success with post‐conflict democratisation missions has opened space for renewed research on three strands of 'deeper democracy': decentralisation, participation and deliberation. This article reports on the study of deliberative democratic practices in emerging governance networks in Prishtina. Through an investigation of three contentious issues in Prishtina's public spaces, research combines documentary sources with field interviews with governance actors to identify factors that enable and constrain the scope for deliberative decision‐making in governance networks. Case studies point to six main influences: 'securitisation', trust building, 'mandate parallelism', structural patterns of inclusion and exclusion, network structures and the properties of governed public spaces. In addition, two frames are found to be particularly resistant to deliberative engagement: Kosovo's status and ethnic identities. We formulate a tentative conclusion to be further investigated: in contexts where distrust is high, deliberative governance requires a rigid adherence to an overarching reference framework that can create discursive space within which relative deliberation can take place. Copyright © 2017 John Wiley & Sons, Ltd.